Colonial Intimacies : Indian Marriage in Early New England - Plane, Ann Marie, 1964- (Book collections on Project MUSE., 2000)
"Native American marital relations and domestic lives were anathema to English Christians: elite native men frequently took more than one wife, while other men and women could dissolve their marriages and take new partners with relative ease. Native marriage did not necessarily involve cohabitation, the formation of a new household, or mutual dependence for subsistence. Couples who wished to separate did so without social reproach, and when adultery occurred, the blame centered not on the "fallen" woman but on the interloping man. Over time, such practices changed, but the emergence of new types of "Indian marriage" enabled the legal, social, and cultural survival of New England's native peoples." "The complex interplay between colonial power and native practice are treated with subtlety and wisdom in Colonial Intimacies. Ann Marie Plane uses travel narratives, missionary tracts, and legal records to reconstruct a previously neglected history."--Jacket.